2014
DOI: 10.1017/s1468109914000152
|View full text |Cite
|
Sign up to set email alerts
|

Governance Innovations and Citizens’ Trust in Local Government: Electoral Impacts in China's Townships

Abstract: We surveyed 2,221 rural residents in twenty towns across ten provinces in China. Structural equation models (SEM) found the quality of government, impartiality of institutions, and authoritarian values among citizens are the three main sources of citizens’ trust in local government. Among various types of recent institutional innovation and government reform, only a type that involves citizens in a formal electoral process, called ‘open nomination and direct election (ONDE)’, significantly improved trust in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Many empirical studies have shown that the high levels of political trust in contemporary China can be mainly attributed to the satisfactory institutional and administrative performance of the Chinese government (Wang, ; Zhao and Hu, ; Zhong, ), especially when it comes to managing economic development, rather than the fear of the Chinese citizens in expressing their genuine opinion about the authoritarian government (Wang, ). Some local government reform efforts, such as encouraging public participation in elections of local governmental officials, also improved public trust in local government (Ma and Wang, ). Proponents of cultural theories contended that the political culture within a society plays an important and independent role in shaping the public trust in government.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many empirical studies have shown that the high levels of political trust in contemporary China can be mainly attributed to the satisfactory institutional and administrative performance of the Chinese government (Wang, ; Zhao and Hu, ; Zhong, ), especially when it comes to managing economic development, rather than the fear of the Chinese citizens in expressing their genuine opinion about the authoritarian government (Wang, ). Some local government reform efforts, such as encouraging public participation in elections of local governmental officials, also improved public trust in local government (Ma and Wang, ). Proponents of cultural theories contended that the political culture within a society plays an important and independent role in shaping the public trust in government.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a path analysis does not support the significant relationship, the weak positive relationship between negative or confused future orientations and trust in government, as shown in Table 1, was not consistent with our original assumption, and the previous study did not suggest that the negative or confused future orientation reduces trust in government (Šerek et al, 2018). In China, traditional values advocate that citizens should trust the government, follow the government's decisions and allow the government to manage and allocate resources to ensure that efficiency is promoted (Ma & Wang, 2014). As previously mentioned, college students are an important group of citizens who participate in politics (Lattie et al, 2019;Šerek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a gauge of political support and how well the political system works in conjunction with citizen orientation and expectations (Citrin, 1974;Easton, 1965Easton, , 1975, institutional trust 6 generally refers to citizens' confidence and belief in their government and institutions (Hetherington, 1998;Miller, 1974). Citizens' trust in government institutions, it goes without saying, plays a very important role in the national political life of the country (Ma and Wang, 2014). Not only does a high degree of trust provide stability in the system (Easton, 1975), but it allows government agencies to have discretion in policy implementation.…”
Section: Do Authoritarian Values Reduce or Increase Institutional Trust?mentioning
confidence: 99%
“…Even though there is a persisting debate on why institutional trust remains high in authoritarian regimes like China and other non-democratic societies like Vietnam and Singapore (Chen et al, 2004; Ma and Wang, 2014; Shi, 2001; Wang, 2016; Wang and Tan, 2013), authoritarian orientations among citizens are broadly dispersed and deeply entrenched in the cultures of Asian societies, even in those with extensive experience of formal democracy like the Philippines (Boudreau, 2009; Chang et al, 2007; Davidson, 2009; Heryanto and Hadiz, 2005; Park, 1991; Pietsch, 2015). Interestingly, in autocratic and illiberal democratic regimes, a much clearer link exists between pro-democratic values leading to lower institutional trust (Chen, 2017; Chen and Dickson, 2008; Ma and Yang, 2014; Shi, 2001).…”
Section: Introductionmentioning
confidence: 99%